Estudo comparativo do efeito da fotobiomodulação vascular com a local em modelo experimental de rinite alérgica induzida por ovoalbumina - Schapochnik, Adriana (2021)
Allergic Rhinitis (AR) is defined as inflammation and/or dysfunction of the nasal mucosa and is a global health problem that has a significant impact on quality of life and the burden of medical care patient education based on better communication can facilitate the control and prevention of allergic rhinitis. The symptoms of AR negatively affect the patient and decrease their productivity. The goal of AR treatment is symptom relief and includes nasal saline irrigation, oral and intranasal decongestants, oral antihistamines, intranasal corticosteroids, leukotriene receptor antagonists, and immunotherapy. However, some of these drugs have considerable side effects, and in more severe cases they are not effective. Thus, Photobiomodulation (PBM) emerges as an adjuvant therapy, without adverse effects and presents good results for several diseases with an inflammatory character, including those of the respiratory tract. Considering that AR is not just a disorder located in the nose and nasal cavities and has a systemic component, this project aims to compare the effects of Vascular PBM (VPBM) in the caudal and Local artery (LPBM) under the nostril with a device. LED (Light Emitting Diode) on the development of AR. For this purpose, adult male Wistar rats were submitted or not to RA by intradermal injections of Ovalbumin (OVA) plus aluminum hydroxide as an adjuvant dissolved in saline solution (from day 1 to 13). After immunization, nasal challenge was performed from day 14 to 21 through daily intranasal instillation of OVA. Rats treated with VPBM and LPBM were irradiated with LED apparatus in the tail artery and nostril for 3 consecutive days immediately after OVA challenge. Our results showed that treatment with VPBM, reduced the level and gene expression of IL-4, increased IL-10 without altering IL-5 and IFN-gamma, and reduced Th2, a cytokine which contribute to improving the symptoms of AR. In this context, the proposed study provided subsidies to propose an effective therapeutic alternative for the treatment of AR with LPMB and not VPMB which does not show any additive effect that justifies its use.